Leadership Policy and Empowerment of Human Resources in Production Houses in Jakarta - Libriantono, Bambang (The International Journal of Education Management and Sociology, 2023)
The purpose of this research is to determine leadership policies in empowering employees and the demands of the world of the creative industry on production houses engaged in television, film, advertising production, and company profiles. Research method with a qualitative approach that describes the phenomenon of events at production house locations. Collection techniques were obtained through field observations, in-depth interviews with key respondents who understand the problem, documentation studies in the form of existing archives and scenario notes, and focus group discussions on the data obtained, discussed together with the existing crew. The research results show that production house leaders want a policy to empower their human resources, so they can meet company needs and customer demands, but are often constrained by work demands, production deadlines, and employee working hours, as well as technology and other factors. Leader policies in implementing production house management to improve the company through empowering Human Resources. Policies that have been implemented include employee protection, strengthening employee systems, and support and maintenance.